Características da função quadrática e a metodologia de resolução de problemas - Assis, Victor Hugo Duarte de [UNESP] (2015)
Teaching of Mathematics craves change methodologies and these are set out in National Curriculum Parameters, in particular, the Troubleshooting methodology introduced by George Polya early last century. Today this methodology is studied by many researchers and is indicated in the curriculum of the State of São Paulo. The objectives of this work are summarized in theory support the properties of quadratic function to obtain your chart; present aspects of the methodology Troubleshooting and results of its application in the third year of high school for teaching quadratic function